To solve for x, we first simplify both sides of the equation:
x(8 + 2) + 3 = 2(5 + x) + 5(x + 1) − 6
Start by simplifying each side individually:
(8 + 2)x + 3 = 2(5 + x) + 5(x + 1) − 6
10x + 3 = 2(5 + x) + 5(x + 1) − 6
Next, distribute the 2 and 5:
10x + 3 = 10 + 2x + 5x + 5 - 6
Combine like terms:
10x + 3 = 7x + 9
Subtract 7x from both sides:
10x + 3 - 7x = 7x + 9 - 7x
3x + 3 = 9
Subtract 3 from both sides:
3x + 3 - 3 = 9 - 3
3x = 6
Divide by 3 on both sides:
x = 6/3
x = 2
The solution for x is 2.
Therefore, the answer is B: -2.
Solve for x:
x(8 + 2) + 3 = 2(5 + x) + 5(x + 1) − 6
Responses
A −4−4
B −2−2
C 22
D 4
1 answer